INFLUENCE OF MOBILE BANKING SERVICE THE NUMBER OF CUSTOMERS BANK ACEH ISLAMIC KCP BATUPHAT, LHOKSEUMAWE - Fitriyani, Ema; Husni Kamal; Mukhtasar (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
This research aims to determine and analyze whether there is influence of mobile banking services on the number of customers of Bank Aceh Syariah KCP Batuphat. In this study using primary data obtained from distributing questionnaires, where the population in this study was 997 mobile banking action users, the data was obtained from Bank Aceh Syariah KCP Batuphat. The samples in this study were 90 mobile banking action users. The data used accidental sampling technique, which tested using validity test, reliability test, classic assumption test, multiple determination test (R2), partial test, simultaneous test, simple regression test. As for the results of testing the hypothesis in this study, namely, the partial test results show a t-count value of 6,907 > t-table (1,987) and a significant value of 0,000 <0.05 so that mobile banking services have a positive and significant effect on the number of customers. The results of the multiple determination test (R2) show that the value of R2 is 0.569, meaning that the contribution of mobile banking services to the variable number of customers is 56.5%. The results of simple linear regression show that there is an effect of mobile banking services on the number of customers with a value of 0.149 or 14.9%.